Intellectual property rights and foreign direct investment: A disaggregated analysis - Peter Nunnenkamp; Julius Spatz (Review of World Economics, 2004)
This paper aims at overcoming several shortcomings of previous empirical studies on the relationship between IPR protection and FDI. First of all, we use sectorally disaggregated FDI data for a large sampie of host countries. Second, we address the proposition that stronger IPR protection raises not only the quantity but also the quality of FDI. Third, we check to which extent the relationship between IPR protection and FDI is affected by applying alternative measures of IPR protection. Our empirical findings support the hypothesis that the threat of an unauthorized use of intellectual-property-reiated assets and, thus, FDI depends on industry as weIl as host-country characteristics. Furthermore, stronger IPR protection may help induce high-quality FDI.
Keywords: 330; Immaterialgüterrechte; Patentrecht; Direktinvestition; Wirtschaftsstruktur